2002
DOI: 10.1007/s10050-002-8764-7
|View full text |Cite
|
Sign up to set email alerts
|

ω-meson photoproduction on nucleons in the near-threshold region

Abstract: The ω-meson photoproduction, γ + p → p + ω, is studied in the framework of a model, containing π-meson exchange in t-channel and nucleon-exchange in s-and u-channels. Considering both ωN N -coupling constants in the region of time-like meson four momenta as the free parameters, we find different sets of solutions for these constants from the existing data on the t-dependence of the differential cross sections, dσ(γ + p → p + ω)/dt, in the near threshold region E γ ≤ 2 GeV. These sets of ωN N -coupling constant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 17 publications
(23 reference statements)
1
13
0
Order By: Relevance
“…The obtained g πN N =12.85 is slightly lower than found in other analysis, for example by SAID group [41,42]: g πN N =13. 13. Note, however, that the present calculation examines a large energy region using only one πN N coupling constant, thereby putting large constraints through all production channels on this coupling and the threshold region only plays a minor role.…”
Section: B T-channel and Born Contributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The obtained g πN N =12.85 is slightly lower than found in other analysis, for example by SAID group [41,42]: g πN N =13. 13. Note, however, that the present calculation examines a large energy region using only one πN N coupling constant, thereby putting large constraints through all production channels on this coupling and the threshold region only plays a minor role.…”
Section: B T-channel and Born Contributionsmentioning
confidence: 99%
“…In our last analysis of the pioninduced reactions [8] it has been shown that while the spin-states. In the model of Babacan et al [13] resonance contributions to ωN final state have been neglected thereby the reaction process is described by the only nucleon and t-channel production mechanisms. A good simultaneous description of all available experimental data on the (π/γ)N → ωN reactions for √ s 2 GeV has been achieved in our previous study [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…energy, up to W = 2.4 GeV with ∼ 60% of the full production-angle range. Many models, including coupled channel, effective Lagrangian, and QCD-inspired approaches [7][8][9][10][11][12], were developed, trying to explain the behavior of the experimental data. Another high-statistics measurement of the γp → ωp differential cross sections and spin-density matrix elements was recently made by the CLAS Collaboration [13], covering c.m.…”
Section: Introductionmentioning
confidence: 99%
“…They have also been used to extract the ⌬͑1232͒ contribution from the M 1+ 3/2 , E 1+ 3/2 , and S 1+ 3/2 electroproduction multipoles [9]. One of the most popular approaches for constructing photoproduction amplitudes is through the use of effective Lagrangians [10][11][12][13][14][15][16][17][18]. Typically, the tree level amplitudes obtained from these Lagrangians are unitarized following some prescription so as to satisfy Watson's theorem [19].…”
Section: Introductionmentioning
confidence: 99%